Organizational performance of the KONI Kota Kupang based on leadership style, retention, and work–life balance - Moniche Aletha Saubaki; Luis Marnisah (Institute of Computer Science (IOCS), 2026)
This study aims to analyze and examine the partial and simultaneous effects of leadership style, retention, and work–life balance on organizational performance at KONI Kupang City. The research employs a quantitative method with a survey, confirmatory, and verificative approach. This study is classified as associative research focusing on the relationships among variables. The research population consists of 93 administrators, all of whom were included as the research sample using a saturated sampling technique. The data comprise primary and secondary data, collected through observation, questionnaire-based interviews, and documentation. Data analysis was conducted using multiple linear regression with SPSS version 30. The results indicate that leadership style, retention, and work–life balance have a significant positive effect on improving organizational performance, both partially and simultaneously. These three variables demonstrate a substantial (strong) relationship, accounting for 72.8% of the improvement in organizational performance. This research contributes to developing comprehensive human resource management science and further research in this field. Improving organizational performance can be done by simultaneously paying attention to aspects of leadership style, retention, and work-life balance